2010
DOI: 10.1002/ana.21897
|View full text |Cite
|
Sign up to set email alerts
|

Triptan‐induced latent sensitization: A possible basis for medication overuse headache

Abstract: Objective Identification of the neural mechanisms underlying medication overuse headache resulting from triptans. Methods Triptans were administered systemically to rats by repeated intermittent injections or by continuous infusion over 6 days. Periorbital and hind paw sensory thresholds were measured to detect cutaneous allodynia. Immunofluorescent histochemistry was employed to detect changes in peptidic neurotransmitter expression in identified dural afferents. Enzyme-linked immunoabsorbent assay was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
238
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(259 citation statements)
references
References 65 publications
12
238
0
1
Order By: Relevance
“…We do not know whether druginduced headache indicates a neuronal or vascular mechanism, a threshold or sensitivity effect, or even an allergic or immunological response. Recently, it has been shown that overuse of these medications could induce neural adaptations that result in a state of latent sensitization, which might increase sensitivity to migraine triggers [34]. The latent sensitization could provide a mechanistic basis for the transformation of migraine to medication overuse headache.…”
Section: Discussionmentioning
confidence: 99%
“…We do not know whether druginduced headache indicates a neuronal or vascular mechanism, a threshold or sensitivity effect, or even an allergic or immunological response. Recently, it has been shown that overuse of these medications could induce neural adaptations that result in a state of latent sensitization, which might increase sensitivity to migraine triggers [34]. The latent sensitization could provide a mechanistic basis for the transformation of migraine to medication overuse headache.…”
Section: Discussionmentioning
confidence: 99%
“…Deafferentation is a well-recognized mechanism generating neuropathic pain. Changes in algogenic protein expression in trigeminal ganglia and latent sensitization have been demonstrated in rats chronically exposed to triptans [22]. A derangement of the central serotonin-dependent endogenous pain control system induced by chronic medication has been proposed [16].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CGRP is a key molecule in migraine pathogenesis. Interestingly, in MOH model animals, triptan increased CGRP levels [11]. In addition, exposure to µ opioids such as morphine also increased CGRP in cultured dorsal root ganglion cells [12,13].…”
Section: Introductionmentioning
confidence: 93%